2018
DOI: 10.32474/oajbeb.2018.02.000126
|View full text |Cite
|
Sign up to set email alerts
|

Novel Techniques for Improving Anti-Cancer Efficacy via Synergistic Phototherapy

Abstract: Factors influencing the cancer therapy efficiency in both photothermal therapy (PTT) and photodynamic therapy (PDT) using nanogold particles and photosensitizers, respectively, are analyzed. In PTT, heat diffusion kinetics is used to calculate the temperature increase resulted from the nanogold absorption of light energy, whereas photochemical kinetics is used to find the efficacy of PDT, or the generation rate of reactive oxygen species. Efficacy of cancer therapy may be enhanced by combining PTT and PDT eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…A generalized, time dependent Beer-Lambert law (BLL), the non-BRL optimal conditions, and mathematical formulas (scaling laws) have been discussed by Lin [26][27][28]. Similar to the synergic efficacy of PDT/PTT [6], far infrared light (3 to 50um) can cause the selective absorption of biological lipid bilayer membranes to enhance the overall LLLT efficacy, via the synergic activation of light/heat sensitive ion channels. Figure 1 shows the PDT efficacy versus light dose (E) and photosensitizer (PS) concentration, C 0 .…”
Section: The Efficacy and Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…A generalized, time dependent Beer-Lambert law (BLL), the non-BRL optimal conditions, and mathematical formulas (scaling laws) have been discussed by Lin [26][27][28]. Similar to the synergic efficacy of PDT/PTT [6], far infrared light (3 to 50um) can cause the selective absorption of biological lipid bilayer membranes to enhance the overall LLLT efficacy, via the synergic activation of light/heat sensitive ion channels. Figure 1 shows the PDT efficacy versus light dose (E) and photosensitizer (PS) concentration, C 0 .…”
Section: The Efficacy and Mechanismsmentioning
confidence: 99%
“…Lights (lasers and LEDs) have been used for various medical procedures such as dermatology and cosmetic surgery, wound healings, nerve stimulation, dentistry ophthalmology applications for vision corrections and corneal deceases, and many other therapeutic procedures [1][2][3]. Combining the nanoparticles, diode lasers have been also used for cancer therapy, bio-sensing, bioimaging, drug delivery, tissue engineering and diagnostics of cancer cell [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review article of Yurt & Tuncel [1] reported the clinical aspects of combined photodynamic and radiotherapy synergistic effect in cancer treatment. Synergic method combining photothermal therapy (PTT) and photodynamic therapy (PDT) using nanogold particles and photosensitizers were also reported [2][3][4]. Besides the synergic methods, improvement of the efficacy of anti-cancer also include the use of nano-medicine and nanoparticles [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, type II photoinitiator requires a coinitiator and often accelerant species to generate efficiently a sufficient number of radicals for photopolymerization. The kinetic of PPS and its clinical applications for anti-cancer [10][11][12][13] and corneal crosslinking (CXL) [14,15] have been recently presented. We have presented modeling the efficacy profiles of UV-light activated CXL, in which the treated cornea has a much smaller thickness (approximately 500 um, or 0.05 cm) than most polymer systems, approximately 1.0 cm.…”
Section: Introductionmentioning
confidence: 99%